DEVELOPMENT OF A BPJS HOSPITAL CLAIMS MONITORING SYSTEMS VIA BRIDGING DASHBOARD - Lesmana, Asep; Taufik, Andi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Enhancing efficiency in the management of claims by the Social Security Organizing Agency (BPJS) at hospitals is a paramount issue in the healthcare sector. This research endeavors to address this challenge by proposing the implementation of Dashboard Bridging, a technology-based solution capable of integrating data from various information sources within hospitals. This system generates comprehensive real-time information and enables more precise decision-making in the management of BPJS claims. Through a structured development approach, the Dashboard Bridging system is designed and implemented to ensure accuracy and optimal performance in BPJS claim analysis. Its objectives include reducing claim processing time, improving healthcare service quality, and potentially enhancing hospital operational efficiency. Furthermore, it aims to serve as a reference for the development of similar solutions in various public service sectors.